2019
DOI: 10.1021/acs.jpcc.9b07358
|View full text |Cite
|
Sign up to set email alerts
|

Oriented External Electric Fields Affect Rate and Stereoselectivity of Electrocyclic Reactions

Abstract: We carried out a computational investigation at the density functional theory (M06-2X) level on the effects of oriented external electric fields (OEEF) on activation barriers and stereochemical output of the thermal ring opening of 3-substituted cyclobutenes (C4H5X) to butadienes. It is well known that with πelectron-donor substituents (X = CH 3 , NH 2 ), the conrotatory outward rotation is preferred, while with π-electron-acceptor substituents (X = CHO, NO, BH 2 ), the conrotatory inward process becomes favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Consequently, the geometric and electronic modification of cisplatin under different oriented external electric fields (OEEFs) has been detailedly studied in this work. It is recently reported that OEEFs can cause structural distortions, 18,19 induce proton transfer, 20,21 modulate NLO responses of materials, 22,23 and catalyze various reactions as smart catalysts and controllers of reaction mechanisms 24–33 . Herein, we will mainly focus on the following two questions: (a) What is the influence of OEEFs on the geometric and electronic structure of cisplatin?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the geometric and electronic modification of cisplatin under different oriented external electric fields (OEEFs) has been detailedly studied in this work. It is recently reported that OEEFs can cause structural distortions, 18,19 induce proton transfer, 20,21 modulate NLO responses of materials, 22,23 and catalyze various reactions as smart catalysts and controllers of reaction mechanisms 24–33 . Herein, we will mainly focus on the following two questions: (a) What is the influence of OEEFs on the geometric and electronic structure of cisplatin?…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that OEEFs can cause structural distortions, 18,19 induce proton transfer, 20,21 modulate NLO responses of materials, 22,23 and catalyze various reactions as smart catalysts and controllers of reaction mechanisms. [24][25][26][27][28][29][30][31][32][33] Herein, we will mainly focus on the following two questions: (a) What is the influence of OEEFs on the geometric and electronic structure of cisplatin? (b) How does the OEEF-induced geometric and electronic modification improve the antitumor activity of cisplatin in electrochemotherapy?…”
mentioning
confidence: 99%
“…First, in the studied photocatalytic reactions, it induces polarization of molecules, which in turn enhances their reactivity. The profound impact of the electric field, in particular an oriented external electric field, on the reactivity of molecules has been studied theoretically and confirmed experimentally. Second, the concentration of the internal electric field in the nanotube induced by the confinement effect facilitates separation of the photogenerated charge carriers and extends their lifetime (Figure f). As a result, photogenerated electrons and holes are utilized more efficiently, which leads to a higher AQY (Figure d).…”
Section: Discussionmentioning
confidence: 84%
“…This is in line with the acknowledged importance of the induced dipole in tuning the catalytic effect of external fields in reactivity. 28,52 For the highest strength E-field considered of 1.5 × 10 8 V/cm, the energy lowering from the induced dipole is more than double the maximum energy variation due to the permanent dipole. Overall, in all systems the energy lowering effect of the induced dipole acts to: i) increase the energy lowering of the permanent dipole when the molecular dipole is aligned with Fx, and ii) largely cancel the energetically destabilising effect of the permanent dipole (or even reverse it at high field) when the molecular dipole is anti-aligned with Fx.…”
Section: Resultsmentioning
confidence: 98%